Poverty measurement and decomposition of aggregate poverty change in the Philippines - Fajardo-Duka, Marichu (Philippine Review of Economics and Business (formerly The Philippine Review of Business and Economics), 1992)
Poverty assessment is influenced by how the issues on the definition and measurement of poverty are addressed. These conceptual issues include: the choice of welfare indicator, the determination of the poverty line, the unit of analysis, the choice of equivalence scales and the choice of poverty index. Using the household data set of the Family Income and Expenditures Survey, this study illustrates that the incidence of poverty differs, depending on the choice of poverty index. Given a change in the poverty incidence between 1985 and 1988, this paper examines the factors underlying the observed change through the use of a decomposition method. This method quantifies the relative contribution of economic growth and changes in inequality to changes in poverty. The results indicate that the growth component at a given level of consumption largely contributes to the overall poverty reduction.